THE ROLE OF HEDONISM IN THE RELATIONSHIP BETWEEN PRODUCT CHARACTERISTICS, MARKETING CHARACTERISTICS, AND CONSUMER CHARACTERISTICS TOWARDS IMPULSIVE BUYING BEHAVIOR - Irwan Christanto Edy; Setyani Sri Haryanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study to determine the factors that influence the behavior Impulsive buying This study is a survey research. The data used are primary data and secondary student population of the city of Surakarta as research objects. Data collection instrument in the form of a list of questions (questionnaire) both with closed questions. Data analysis methods used include 1) analysis of test instruments that test the validity and reliability test, 2) descriptive statistical analysis, 3) analysis by SEM-PLS models. These results indicate that (1) the product characteristics of the most dominant influence impulsive behavior, (2) Goodness of fit model by 51% (for R-Square = 0.51), meaning that the model is sound and Impulsive buying behavior is influenced by the characteristics of the product, marketing and consumer by 51%, and the rest 49% influenced by other factors not examined, (3) Hedonism less effective mediating influence the characteristics of the product, marketing and consumers against buying Impulsive Behavior